Extending Hate Crime Legislation to Include Gender: Explicating an Analogical Method of Advocacy - Berard, Tim J. (Qualitative Sociology Review, 2005)
This paper examines expert testimony advocating the inclusion, in proposed hate-crime legislation, of crimes motivated by gender bias. The design and rhetoric of such testimony evidences formal properties. Precisely because these properties are formal properties, not limited to specific cases or issues, their explication will contribute not only to the understanding of hate crimes discourse, but to social problems research and theory more broadly. Arguments for the expansion of rights to previously unprotected categories (1) can be designed with an emphasis on generic or formal principles, which allow for the inclusion of previously unprotected groups whose victimization constitutes additional social problems not yet institutionally recognized. Such arguments (2) can emphasize parallelism between protected categories and unprotected categories, and between recognized social problems and as-yet-unrecognized social problems, making similar institutional treatment seem rational, and making disparate treatment seem unjustifiable or insensitive. And such arguments (3) can propose limits to the desired expansion of rights, as a means of pre-empting “floodgate” arguments against expanding the scope of existing protections. More generally, membership categorization analysis is employed to study social identity and inter-group relations as these are constituted in social problems discourse. Special reference is made in this case to “hate crimes” and how they might be addressed by membership categorization analysis in the context of constructionist social problems analysis and qualitative sociolegal studies.